Pengaruh Kompetensi SDM terhadap Kinerja Karyawan yang Dimediasi oleh Komitmen: Studi pada Lembaga KSPPS. BMT NU Jatim Cabang Lenteng Kabupaten Sumenep - Chamariyah Chamariyah; Wasis Budiarto; Imam Afifi Raqib (Universitas 45 Surabaya, 2025)
Imam Afifi Raqib, 2024. The Effect of HR Competence on Employee Performance Mediated by Commitment (Study at KSPPS Institution. BMT NU Jatim Lenteng Branch Sumenep Regency). Postgraduate Program at Wijaya Putra University Surabaya. This type of research is explanatory research, the approach used is a quantitative approach, the research sample is 50 people. The analysis tool uses Smart PLS (Partial Least Square). Research objectives: 1) To determine and analyze whether HR competence has an influence on the performance of employees of KSPPS Institution. BMT NU JATIM Lenteng Branch Sumenep Regency. 2) To determine and analyze whether HR competencies have an influence on the commitment of the KSPPS Institution. BMT NU JATIM Lenteng Branch Sumenep Regency. 3) To determine and analyze whether commitment has an influence on employee performance KSPPS Institution. BMT NU JATIM Lenteng Branch Sumenep Regency. 4) To determine and analyze whether HR competence has an indirect influence on employee performance mediated by the commitment of the KSPPS Institution. BMT NU JATIM Lenteng Branch Sumenep Regency. The results showed that: 1) HR competence has a significant positive effect on employee performance as evidenced by the original sample value of 0.264 and p-values of 0.029. 2) HR competence has a significant positive effect on commitment as evidenced by the original sample value of 0.410 and p-values of 0.000. 3) Commitment has a significant positive effect on employee performance as evidenced by the original sample value of 0.310 and p-values of 0.026. 6) HR competence has no positive and significant effect on performance mediated by commitment as evidenced by the original sample value of 0.127 and p-values of 0.065.